Correlation between point load index and compressive strength for quartzite rocks - Singh V.K.; Singh D.P. (My University, 2025)
The relationship of the point load test with uniaxial compressive strength was examined using quartzite rocks to substantiate the existing correlations. © 1993 Chapman & Hall.